Postracial Resistance : Black Women, Media, and the Uses of Strategic Ambiguity - Joseph, Ralina L. 1974-; Joseph, Ralina L. 1974- (Book collections on Project MUSE., 2018)
Introduction -- Of course I'm proud of my country! : Michelle Obama's post-racial wink -- Because often it's both : racism, sexism, and Oprah's handbags -- I just wanted a world that looked like the one I know : the strategically ambiguous respectability of a Black woman showrunner -- No, but I'm still black : women of color community, hate-watching, and racialized resistance -- They got rid of the naps, that's all they did : women of color critiques of respectability politics, strategic ambiguity, and race hazing -- Do not run away from your blackness : Black women television workers and the flouting of strategic ambiguity -- Coda : have a seat at my table -- Acknowledgments -- Notes -- Works cited -- Index -- About the author